427 RECOVERY OF SPERMATOGENESIS AFTER ANDROGEN-PROGESTIN THERAPY. (1st January 2006) - Liu, P. Y.; Swerdloff, R. S.; Wang, C.
Abstract : Context: Male hormonal contraceptive methods are approaching market. Factors predicting the reversibility of these methods have not been systematically examined. Objective: To determine the time and potential modulating covariables required for sperm density to recover to normal after androgen or androgen-progestin therapy sufficient for contraceptive purposes and to characterize other semen parameters as sperm density recovers. Design: An integrated multivariate stepwise and best-subset Cox proportional hazards analysis of all published studies of at least 3 months' treatment duration. Individual subject, not just summary, data were directly collected from individual investigators concerning studies published 1990-2005, which assessed subjects monthly until sperm density recovered to normal (to 20 M/mL). Setting: 29 separate studies spanning the globe. Participants: 1, 549 normal (by physical, blood, and semen exam) men aged 19-51 years of predominantly Caucasian (two-thirds) or Asian (one-third) descent. This represents 1, 283.5 patient years of treatment and 705 patient years of recovery and includes > 97% of all the published data. Intervention(s): Men were treated with testosterone (T) with or without progestin for 3 to 18 months. Results: Sperm density recovered to normal after 3.4 (3.2-3.5 95% CI) months in 50% of all subjects (Kaplan-Meier). Slower recovery occurred with very prolonged treatment, Caucasian ethnicity, and with longer-acting T preparations. For a typical male, aged 35 years of Caucasian descent, treated for 1 year with intramuscular T undecanoate, the median recovery time was 4.6 (4.1-5.0) months. These times were 4.1 (3.9-4.6), 5.3 (4.9-6.3), and 3.0 (2.8-3.6), months if the male was of Asian descent, treated for 1.5 years, or treated with T enanthate, respectively. Faster recovery was predicted by greater age, faster suppression of spermatogenesis, higher baseline sperm density, and lower baseline blood LH; however, although significant, these adjusted-effect sizes were small. From multivariate model analyses, the probability of recovery within 6, 12, 16, and 24 months was 67 (61-72), 90 (85-93), 96 (92-98), and 100%, respectively. Recovery to lower sperm thresholds (3 M/mL and 10 M/mL) tracked recovery to 20 M/mL and sperm morphology and motility closely followed recovery of sperm density. Conclusion: We have identified important predictors and quantified expected probabilities of recovery. This is critical for the utilization of male hormonal contraceptive regimens.